Mimicking the electrophysiological microenvironment of bone tissue using electroactive materials to promote its regeneration. Issue 45 (21st October 2020) - Zheng, Tianyi; Huang, Yiqian; Zhang, Xuehui; Cai, Qing; Deng, Xuliang; Yang, Xiaoping
Abstract : A timely and comprehensive account of electroactive biomaterials promoting bone regeneration is provided by reviewing their physicochemical and biological properties. Abstract : The process of bone tissue repair and regeneration is complex and requires a variety of physiological signals, including biochemical, electrical and mechanical signals, which collaborate to ensure functional recovery. The inherent piezoelectric properties of bone tissues can convert mechanical stimulation into electrical effects, which play significant roles in bone maturation, remodeling and reconstruction. Electroactive materials, including conductive materials, piezoelectric materials and electret materials, can simulate the physiological and electrical microenvironment of bone tissue, thereby promoting bone regeneration and reconstruction. In this paper, the structures and performances of different types of electroactive materials and their applications in the field of bone repair and regeneration are reviewed, particularly by providing the results from in vivo evaluations using various animal models. Their advantages and disadvantages as bone repair materials are discussed, and the methods for tuning their performances are also described, with the aim of providing an up-to-date account of the proposed topics.